An efficient microwave-assisted synthesis and biological properties of polysubstituted pyrimidinyl- and 1,3,5-triazinylphosphonic acids - Jansa, Petr (Tetrahedron, 2012)
Polysubstituted pyrimidinylphosphonic and 1,3,5-triazinylphosphonic acids with potential biological properties were prepared in high yields by the microwave-assisted Michaelis–Arbuzov reaction of trialkyl phosphite with the corresponding halopyrimidines and halo-1,3,5-triazines, respectively, followed by the standard deprotection of the phosphonate group using TMSBr in acetonitrile. 4,6-Diamino-5-chloropyrimidin-2-ylphosphonic acid (7a) was found to exhibit a weak to moderate anti-influenza activity (28–50 μM) and may represent a novel hit for further SAR studies and antiviral improvement.